The message of Ezra and Haggai : building for God - Fyall, Robert S. (Downers Grove, Ill. : Inter-Varsity Press, 2010)
This commentary by Robert Fyall highlights the contemporary parallels of the challenges Israel faced to those of today's church and demonstrates the relevance of the books of Ezra and Haggai for God's people in all times.--From publisher description.
Ezra. The ransomed of the Lord return (1:1-11) ; What's in a name? (2:1-70) ; Getting priorities right (3:1-6) ; Starting to take shape (3:7-13) ; The vultures gather (4:1-24) ; God's work cannot be stopped (5:1-17) ; The king and the King (6:1-22) ; God's man arrives (7:1-10) ; The king's heart is in the hand of the Lord (7:11-28) ; Another exodus (8:1-36) ; Faithless people; faithful God (9:1-15) ; Not a happy ending (10:1-44) -- Haggai. When are we to build? (1:1-2) ; A wake-up call (1:3-11) ; At the centre (1:12-15) ; Better days are coming! (2:1-9) ; Count your blessings (2:10-19) ; The best is yet to be (2:20-23)
Includes bibliographical references (p. 13-14)
Keywords: Bible. -- Commentaries; Bible. -- Commentaries